Interdisciplinary ESP course design for tertiary engineering students using professionally oriented situations - Kalkayeva, Aizhan; Golovchun, Aleftina; Irgatoglu, Aydan; Turlybekova, Anar; Ferens, Yulia (Jurnal Cakrawala Pendidikan, 2025)
This research article presents results of an educational experiment based on applying an English for Specific Purposes (ESP) course tailored for university engineering majors using professionally oriented situational tasks. The distinguishing feature of the course is its interdisciplinary nature. It is not limited to one particular field of engineering but comprises various engineering topics suitable for different technical specialties. The study aimed at identifying the commonly encountered workplace situations in which engineers from various subindustries need to apply English, modelling situational tasks integrated in a multi-disciplinary engineering ESP course, and testing the pedagogical effectiveness of the designed model. The experiment was carried out at one of the best technical universities in Kazakhstan, Satbayev University. It encompassed 60 first-year bachelor students majoring in different engineering specialties, including 30 students from an experiential group. A mixed-methods approach based on both qualitative and quantitative methods was exploited that comprised review and investigation of literature, needs analysis questionnaire among alumni of technical universities, evaluation and adaptation of existing ESP coursebooks, didactic modelling, pedagogical experiment, and comparative analysis and mathematical statistics. The findings show superior efficiency of the suggested interdisciplinary Engineering ESP course over a traditional Professional English course.